Amorphous F‐doped TiOx Caulked SnO2 Electron Transport Layer for Flexible Perovskite Solar Cells with Efficiency Exceeding 22.5%. (3rd January 2023) - Zhang, Linghui; Fu, Chao; Wang, Shi; Wang, Minhuan; Wang, Ruiting; Xiang, Shengling; Wang, Zhiyong; Liu, Jing; Ma, Hongru; Wang, Yudi; Yan, Ying; Chen, Min; et al.
Abstract: Flexible perovskite solar cells (f‐PSCs) show great promise in portable‐power applications (e.g., chargers, drones) and low‐cost, scalable productions (e.g., roll‐to‐roll). However, in conventional n–i–p architecture f‐PSCs, the low‐temperature processed metal oxide electron transport layers (ETLs) usually suffer from high resistance and severe defects that limit the power conversion efficiency (PCE) improvement of f‐PSCs. Besides the enhancement in the mobility of metal oxide and passivation for perovskite/ETL interfacial defects reported in previous literature, herein, the electron transport loss between the metal oxide nanocrystallines within the ETL is studied by introducing an amorphous F‐doped TiOx (F‐TiOx ) caulked crystalline SnO2 composite ETL. The F‐TiOx in this novel composite ETL acts as an interstitial medium between adjacent SnO2 nanocrystallines, which can provide more electron transport channels, effectively passivate oxygen vacancies, and optimize the energy level arrangement, thus significantly enhancing the electron mobility of ETL and reducing the charge transport losses. The composite ETL‐based f‐PSCs achieve a high PCE of 22.70% and good operational stability. Furthermore, a moderate roughness of the composite ETL endows f‐PSCs with superior mechanical reliability by virtue of a strong coupling at the ETL/perovskite interface, by which the f‐PSCs can maintain 82.11% of their initial PCE after 4000 bending cycles. Abstract : The study introduces an amorphous F‐TiOx caulked crystalline SnO2 composite ETL. The F‐TiOx provides more electron transport channels, passivates oxygen vacancies, and fine‐tunes the energy level arrangement, thus enhancing the electron mobility of ETL and reducing the charge transport losses. The composite ETL‐based f‐PSCs achieve a high PCE of 22.70%, together with enhanced operational stability and mechanical reliability.